KERAGAAN PASAR KERJA PERTANIAN-NONPERTANIAN DAN MIGRASI DESA-KOTA: TELAAH PERIODE KRISIS EKONOMI - DESSY ADRIANI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
The objectives of this research are: 1) to analyze factors effecting labor marketperformance; 2) to analyze factors effecting migration in Indonesia. The research used poolingdata and be analyzed using simultaneous equation with 2 SLS technique. The result showed thatlabor force is influenced by productive-age population in both urban and rural area. In ruralarea, rural-urban migration also influenced labor force. Demand for labor is influenced by GrossDomestic Product, Labor Intensive Program in urban area, and Infrastructure DevelopmentProgram for Developing Village in rural area. Labor productivity is influenced by sectoral realwage, calorie consumption and Social Safety Net Program for health sector. Sectoral real wageis influenced by Sectoral Minimum Wage and rate of inflation. The result also showed thatsectoral real wage is not the important factor on labor market in Indonesia economic crisis.